Irmédi-Molnár Lászlóhoz - Herodek Károly (Fond 165 Irmédi-Molnár László)
Fond 165 Irmédi-Molnár László > Irmédi-Molnár László iratai. > Irmédi-Molnár László levelezése. > Irmédi-Molnár Lászlóhoz írott levelek.